Digital Literacy of Santri as a New Paradigm of Islamic Education in the Era of Globalization - Kandiri; Fathur Rahim; Supriadi; Hosaini; Shahzadi Hina (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
This study aims to analyze digital literacy as a new paradigm of Islamic education in the era of globalization at Salafiyah-Syafi’iyah Sukorejo Islamic Boarding School. The rapid development of information and communication technology has encouraged Islamic educational institutions to transform their learning processes while maintaining Islamic values and the long-established traditions of pesantren. This research employed a qualitative approach using a case study method. Data were collected through observation, in-depth interviews with pesantren administrators, teachers, and students, as well as document analysis. The data were analyzed through data reduction, data display, and thematic conclusion drawing. The findings reveal that digital literacy has become an essential component in developing students’ competencies through the utilization of digital media, online learning platforms, and access to technology-based Islamic knowledge resources. The implementation of digital literacy not only enhances students’ academic abilities but also strengthens critical thinking skills, information evaluation capabilities, and digital ethics in accordance with Islamic values. However, challenges remain, including disparities in digital competencies, the need for effective technology supervision, and the risk of exposure to unreliable information. The study implies the necessity of developing an integrative Islamic education model that combines pesantren traditions, digital literacy, and Islamic character development to sustainably respond to the challenges of globalization.